2022
DOI: 10.3390/vetsci9050204
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Immunohistochemical Evaluation of Canine Nerve Sheath Tumors and Proposal for an Updated Classification

Abstract: Nerve sheath tumors are a group of tumors originating from Schwann cells, fibroblasts, and perineurial cells. In veterinary pathology, the terminology for nerve sheath tumors remains inconsistent, and many pathologists follow the human classification of such tumors in practice. Immunohistochemistry plays an important role in the diagnosis of nerve sheath tumors, but specific immunohistochemical and molecular biomarkers are lacking. In our study, we histopathologically reevaluated 79 canine nerve sheath tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 58 publications
(84 reference statements)
1
20
1
1
Order By: Relevance
“…Unfortunately, we lacked data on the proliferation marker Ki-67 for 17 of the included tumors, 16 of which were malignant and one benign. According to our previous study, staining of these samples was assessed as unreliable, probably due to poor antigen preservation in old archive blocks (19,25). Previous studies from human pathology have found loss of H3K27me3 expression in a higher percentage of MNSTs, but results vary depending on the study.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Unfortunately, we lacked data on the proliferation marker Ki-67 for 17 of the included tumors, 16 of which were malignant and one benign. According to our previous study, staining of these samples was assessed as unreliable, probably due to poor antigen preservation in old archive blocks (19,25). Previous studies from human pathology have found loss of H3K27me3 expression in a higher percentage of MNSTs, but results vary depending on the study.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we immunohistochemically investigated the expression of H3K27me3 in 68 canine NSTs that had been diagnosed, classified, and, if malignant, graded based on their histopathologic and IHC features in our previous study (19). We compared the individual histopathological features and IHC staining results for Sox10, claudin-1, GFAP, and proliferation index Ki-67 with H3K27me3 expression to assess the potential diagnostic value of the latter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations